POTENSI PENGEMBANGAN AGROINDUSTRI JAMBU BIJI MERAH DI KABUPATEN BANJARNEGARA - Indrie Ambarsari; Abdul Choliq; Syamsul Bahri (JURNAL LITBANG PROVINSI JAWA TENGAH, 2007)
Banjamegara is one of the regency that developing of pink guava is potential. In connection with acceleration of increasing farmer's income, developing of pink guava must be supporting by manulcture di versification. One of them is processing pink guava into puree. The aimed ofassessment were to know the fanning system and the processing manufacture on pink guava commodity and to knowthe profitable level that was returned. Study has done on June-September 2006 at Kaliwungu village, sub district ofMandiraja. The method was used descriptive analysis for each characteristic sector and the account offeasibility. The financial result showed that manufacture of pink guava on Banjarnegara is worthy to develop. NPV on interest 16% in the amount of Rp. I 05.319.973,IRR 81 % and B/C ratio 1,06. Break event point reached at cost of product Rp. 13.842,- with production capacity 38.550 kg.